2016
DOI: 10.1017/s1041610216000430
|View full text |Cite
|
Sign up to set email alerts
|

Perceived loneliness among older adults with mild cognitive impairment

Abstract: Loneliness is implicated in MCI. The relationship between loneliness and MCI is, at least, partially independent of depression. The implications of these finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
(32 reference statements)
4
12
0
2
Order By: Relevance
“…It is yet to be elucidated whether loneliness and network size are causes or consequences of cognitive impairment. As loneliness was also commonly reported in cognitively impaired older adults (Yu et al, 2016), it was possible that loneliness and a small social network might be the signs of cognitive decline or precipitating factors of underlying neurodegenerative process. A recent novel study found that higher cortical amyloid burden was associated with loneliness in normal healthy older adults, suggesting that loneliness might be an early sign of neurodegenerative disorders and should receive clinical attention (Donovan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is yet to be elucidated whether loneliness and network size are causes or consequences of cognitive impairment. As loneliness was also commonly reported in cognitively impaired older adults (Yu et al, 2016), it was possible that loneliness and a small social network might be the signs of cognitive decline or precipitating factors of underlying neurodegenerative process. A recent novel study found that higher cortical amyloid burden was associated with loneliness in normal healthy older adults, suggesting that loneliness might be an early sign of neurodegenerative disorders and should receive clinical attention (Donovan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness has been linked to poor mental health [e.g., depression, hopelessness, substance use, and cognitive impairment], as well as worse physical health [e.g., malnutrition, worse motor function, hypertension, disrupted sleep, frailty], and higher mortality (Aanes et al, 2011;Boss et al, 2015;Cacioppo et al, 2002;Tabue Teguo et al, 2016;Yu et al, 2016). Biological mechanisms such as dysregulated hypothalamic-pituitary-adrenal axis function and dysregulated immune function have been proposed to mediate the link between loneliness and these poor health outcomes (Cacioppo et al, 2002;van Beljouw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Fung et al (2019) examines loneliness in older Chinese adults and the links with different types of relationships and cognitive functioning. Loneliness is an important social aspect of successful aging, with a number of studies emphasizing its influence on mental and physical health (Aanes et al, 2011;Boss et al, 2015;Cacioppo et al, 2002;Tabue Teguo et al, 2016;Yu et al, 2016). While exploratory, the findings from the Fung et al paper indicate that the interaction between loneliness and a non-confiding social network (i.e., the participants did not feel they could express their inner feelings with their social contacts) were significantly associated with poor cognitive functioning.…”
mentioning
confidence: 99%